2022
DOI: 10.1002/jev2.12197
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma‐derived extracellular vesicles mediate lymphatic remodelling and impair tumour immunity in draining lymph nodes

Abstract: Tumour-draining lymph nodes (LNs) undergo massive remodelling including expansion of the lymphatic sinuses, a process that has been linked to lymphatic metastasis by creation of a pre-metastatic niche. However, the signals leading to these changes have not been completely understood. Here, we found that extracellular vesicles (EVs) derived from melanoma cells are rapidly transported by lymphatic vessels to draining LNs, where they selectively interact with lymphatic endothelial cells (LECs) as well as medullar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 72 publications
0
59
0
Order By: Relevance
“…Tumor-draining inguinal LNs from mice bearing B16F10-luc2 melanomas ( N = 3) were harvested on day 14 for sorting of LECs by FACS and processed in parallel with our previous study for scRNA-seq [ 18 ]. ScRNA-seq data of the naive control is accessible at ArrayExpress under the accession number E-MTAB-10434.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor-draining inguinal LNs from mice bearing B16F10-luc2 melanomas ( N = 3) were harvested on day 14 for sorting of LECs by FACS and processed in parallel with our previous study for scRNA-seq [ 18 ]. ScRNA-seq data of the naive control is accessible at ArrayExpress under the accession number E-MTAB-10434.…”
Section: Methodsmentioning
confidence: 99%
“…Of note, these changes may occur before metastatic colonization of the LNs, indicating the involvement of tumor-derived factors, such as extracellular vesicles (EVs) and soluble growth factors carried by afferent lymph [ 12 , 13 , 14 , 15 ]. Melanoma-derived EVs have been shown to interact directly with LN-resident LECs [ 16 , 17 , 18 ], inducing lymphangiogenesis and subsequent metastasis [ 17 , 18 ]. LN LECs have also been implicated in tumor immune evasion and immunotherapy resistance by cross-presenting tumor-derived antigens [ 19 ] and by expressing the T cell-inhibitory molecule PD-L1 [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, tumor-draining LNs undergo massive remodeling, including accumulation of immunosuppressive cells, reprogramming of stromal cells and vascular remodeling [ 153 155 ]. Leary et al found that extracellular vesicles derived from melanoma cells selectively interact with LN resident macrophages and lymphatic endothelial cells, induce LN remodeling and eventually impair anti-tumor immunity [ 156 ]. Therefore, how to adapt to the changing lymphatic microenvironment should be considered in vaccine development.…”
Section: Challenges Of Self-adjuvanting Nanovaccines For Cancer Therapymentioning
confidence: 99%
“…They showed that sEVs are transported and taken up by LECs in a VCAM-1 dependent fashion, which led to gene expression changes and proliferation in these cells. Additionally, sEVs impaired tumor immunity by shuttling MHC-1 to LECs [95].…”
Section: Lymphangiogenesismentioning
confidence: 99%